Exposure to fungi in cork: potential occupational hazard - Nunes, Ana Carolina (2014)
Cork is a light, porous and impermeable material extracted from the bark of some trees. It is in manufacture of stoppers for wine bottles the main application of cork. It is estimated that the area occupied by cork oaks in the Iberian Peninsula is around 33% in Portugal and 23% in Spain. The world production of cork is focused in the south Europe, with Portugal being the most important producer followed by Spain. According to Companies Directory more than 100 manufactories from Portugal has their branch associated with the preparation and fabrication of cork. Cork workers are at risk for developing diseases of the respiratory tract such as occupational asthma and Suberosis, a form of pulmonary hypersensitivity due to repeated exposure to mouldy cork dust. In this review study papers from 2000 were analyzed to better understand which fungi species are associated with occupational disease in cork workers. The most prevalent fungi species in these workers that are associated with those occupational diseases are Penicilliumglabrum, Chrysoniliasitophila and Trichodermalongibrachiatum. Therefore, a specific knowledge about occupational exposure to fungi in the cork industry is the key to better understand the related diseases and to define preventive measures. Given the importance of this occupational setting in Portugal is essential to evaluate the combined exposure of fungi and particles and their metabolites. Further studies concerning exposure assessment to fungi and particles in the cork industry must be developed.